2015
DOI: 10.1128/jvi.02784-14
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Regulates Apoptosis and Tumorigenesis through the MicroRNA-15a-Smad7-Transforming Growth Factor Beta Pathway

Abstract: Hepatitis B virus (HBV) infection causes chronic hepatitis in hundreds of millions of people worldwide, which can eventually lead to hepatocellular carcinoma (HCC). Previously, we found that HBV mRNAs can absorb microRNA-15a (miR-15a) to affect apoptosis through the Bcl-2 pathway. We asked whether HBV could inhibit apoptosis and promote tumorigenesis through different pathways. In this study, we found that the transforming growth factor ␤ (TGF-␤) pathway-inhibitory factor Smad7 is a novel target of miR-15a. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…The human hepatoma cell line HepG2, human embryonic kidney cell line 293T, human normal liver cell line L02, and Mus musculus neuronal and amoeboid stem cell line Neuro‐2a used in this study were purchased from ATCC (USA). The HepG2‐4D14 cell lines, in which the HBV genome was stably integrated, were kindly provided by Dongping Xu (302 Hospital of PLA, China) …”
Section: Methodsmentioning
confidence: 99%
“…The human hepatoma cell line HepG2, human embryonic kidney cell line 293T, human normal liver cell line L02, and Mus musculus neuronal and amoeboid stem cell line Neuro‐2a used in this study were purchased from ATCC (USA). The HepG2‐4D14 cell lines, in which the HBV genome was stably integrated, were kindly provided by Dongping Xu (302 Hospital of PLA, China) …”
Section: Methodsmentioning
confidence: 99%
“…It has proved that miR-15a has a positive effect on TGF-β/Smad pathway in HBV-infected patients [34]. Hepatitis C virus (HCV) infection causes chronic hepatitis, which may progress to hepatic fibrosis, even HCC.…”
Section: The Mir-15 Family Members Have a Positive Impact On Tgf-β Simentioning
confidence: 99%
“…Studies have shown that HBV and its viral proteins are at least partially responsible for over-activation of TGF-β signaling in HBV-related HCC [13, 14]. Lee et al found that HBx enhanced phosphorylation of pSmad2/3C by binding with Smad4 and amplified TGF-β signal pathway in several HCC cell lines, which led to the enhanced transcriptional activation of TGF-β-responsive genes [15].…”
Section: Introductionmentioning
confidence: 99%